A new species of Eryx (Serpentes: Erycidae) from Iran - Eskandarzadeh, Naeimeh; Rastegar-Pouyani, Nasrullah; Rastegar-Pouyani, Eskandar; Zargan, Jamil; Hajinourmohamadi, Ashkan; Nazarov, Roman A.; Sami, Soheil; Rajabizadeh, Mahdi; Nabizadeh, Hossein; Navaian, Majid (Zootaxa, 2020)
Eskandarzadeh, Naeimeh, Rastegar-Pouyani, Nasrullah, Rastegar-Pouyani, Eskandar, Zargan, Jamil, Hajinourmohamadi, Ashkan, Nazarov, Roman A., Sami, Soheil, Rajabizadeh, Mahdi, Nabizadeh, Hossein, Navaian, Majid (2020): A new species of Eryx (Serpentes: Erycidae) from Iran. Zootaxa 4767 (1): 182-192, DOI:10.11646/zootaxa.4767.1.8